2013
DOI: 10.3109/02652048.2013.770095
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel lipidic nanoparticle probe using liposomal encapsulated Gd2O3–DEG for molecular MRI

Abstract: Recently, it has been showed that gadolinium oxide nanoparticles can provide high-contrast enhancement in magnetic resonance imaging (MRI). Moreover, liposomes due to high biocompatibility have shown unique model systems, with the most successful application being the drug delivery system. As a suitable cell-tracking contrast agent (CA) in molecular MRI (mMRI), the synthesis and optimisation characteristic of a novel paramagnetic liposomes (PMLs) based on gadolinium nanoparticles, essentially composed of a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…From then on, Gd 2 O 3 became the prototype of Gd-based inorganic nanoparticulate T 1 CAs, and the relevant studies were expanding. One facile method for preparing Gd 2 O 3 nanoparticles is through the polyol route, in which polyol agents are utilized as solvents and capping agents. Kondo and co-workers synthesized Gd 2 O 3 nanoparticles via a polyol method, and gelatin was used to form protective colloids .…”
Section: Lanthanide Nanoparticles As Mri Contrast Agentsmentioning
confidence: 99%
“…From then on, Gd 2 O 3 became the prototype of Gd-based inorganic nanoparticulate T 1 CAs, and the relevant studies were expanding. One facile method for preparing Gd 2 O 3 nanoparticles is through the polyol route, in which polyol agents are utilized as solvents and capping agents. Kondo and co-workers synthesized Gd 2 O 3 nanoparticles via a polyol method, and gelatin was used to form protective colloids .…”
Section: Lanthanide Nanoparticles As Mri Contrast Agentsmentioning
confidence: 99%
“…In recent studies, different strategies have been explored pertaining to the design of gadolinium-containing nano-objects. These consisted of either synthesizing crystalline nanoparticles containing gadolinium (gadolinium oxides, 19 fluoride, 20 phosphate 21 , 22 and vanadates 23 ) or functionalizing different types of nanoparticles using gadolinium chelates or ions, either within the structure or on the surface (with liposomes, 24 zeolites, 25 mesoporous silica, 26 , 27 quantum dots, 28 lipid particles, 29 gold nanoparticles, 30 , 31 carbon nanotubes 32 , 33 and ultrasmall polysiloxane 34 , 35 ). Yet, out of all the gadolinium-based compounds described so far, while most have been developed for MRI application, very few have been described as radiosensitizers.…”
Section: Gadolinium a Key Element At The Juncture Between Imaging Anmentioning
confidence: 99%
“…Similarly, the HMON@CuS/Gd 2 O 3 were immersed into different concentration of GSH solution (0, 5, and 10 mM), respectively, and the degradation process was also monitored by ICP tests. As shown in the Figure S1 , the Si ions release percentage reached approximately 28.2% dissolved in GSH solution (GSH = 10 mM), whereas only 15.9% was released in the absence of GSH after 60 h. Additionally, because of the presence of Gd 2 O 3 (Zohdiaghdam et al., 2013 ; Fang et al., 2014 ), the as-prepared NPs were expected to be a promising MRI imaging contrast agent, a finding that was confirmed by in vitro MRI scanning ( Figure 2(B) ). UV–vis spectra results revealed that HMON@CuS and HMON@CuS/Gd 2 O 3 both showed strong absorption in the NIR region, primarily attributed to the CuS nanocrystals ( Figure 2(C) ).…”
Section: Resultsmentioning
confidence: 96%